University students’ perceptions on smiles from strangers of different gender - Mohd Ghazalee, Nur Ameera Najihah; Razali, Khairil Azwar (Kulliyyah of Languages & Management, International Islamic University Malaysia, 2020)
Communication involves verbal and nonverbal communication. However, many people pay less attention to nonverbal communication as people focus more on verbal communication without realizing that human use nonverbal communication as much as using verbal communication in daily life (Lunenburg, 2010). Interestingly, there are differences in showing expressions between male and female (Hess, Adams & Kleck, 2004). Smile is one of the facial expressions that people frequently use in daily life. The differences in showing emotions between male and female can simply be seen through smile and interpretation of smile. This study will present a thematic analysis on differences of interpretation of smile from strangers between male and female. This study aimed to explore on how different gender perceive smile from strangers as well as cultural influences on interpretation of smile. Participants of this study are undergraduates from local and private universities in Malaysia. The participants were selected through purposive sampling technique and followed by snowball sampling technique. From the analysis, it shows that there are a slight difference in interpretation of smile between male and female. The analysis also found that family’s upbringing, religion, environment and culture does influence an individual’s interpretation of smile from strangers. However, it is suggested for the future research to widen the target participants and use face-to-face interview as a method to collect the data.